1884 Compiled Laws of the Hawaiian Kingdom, at 86, Of the Safekeeping of Gunpowder § 354 (1884) - (:unkn) unknown (My University, 1884)
Granted the Minister of the Interior the authority to make regulations on the storing, keeping, and transportation of gunpowder in the Kingdom. Prohibited the violation of these regulations.
Keywords: GUNPOWDER - STORAGE; GUNPOWDER - TRANSPORTATION